The impact of kidney transplantation on insulin sensitivity. (9th February 2017) - Jørgensen, Morten B.; Hornum, Mads; van Hall, Gerrit; Bistrup, Claus; Hansen, Jesper M.; Mathiesen, Elisabeth R.; Feldt‐Rasmussen, Bo
Summary: To investigate the impact of kidney transplantation (KTx) on insulin sensitivity affecting glucose metabolism. 9 nondiabetic patients awaiting living donor KTx were examined prior to transplantation with an oral glucose tolerance test and a 3‐h hyperinsulinaemic–euglycaemic clamp. The clamp was repeated 6 months after KTx. Nine age‐, gender‐ and body mass index (BMI)‐matched individuals with normal kidney function served as controls. Endogenous glucose production and glucose disappearance rate ( N = 6) were measured in a subgroup of patients with corresponding controls. Results presented as mean [range]. Two patients had pretransplant prediabetes, whereas all others had normal glucose tolerance. After KTx, average glucose infusion rate to maintain euglycaemia during clamp declined significantly from 15.1 [9.1–23.7] to 9.8 [2.8–14.6] μmol/kg/min ( P < 0.01) with 20.2 [9.9–33.7] μmol/kg/min in controls. Endogenous glucose production increased from 7.0 [4.8–8.5] to 9.4 [7.4–11.8] μmol/kg/min ( P < 0.05) with 7.0 [−3.8 to 10.1] μmol/kg/min in controls. Glucose disappearance rate was unchanged (18.1 [12.9‐24.5] vs. 17.1 [12.2‐22.7] μmol/kg/min, NS) with 22.3 [14.6–34.3] in controls. In conclusion, insulin sensitivity is reduced 6 months after KTx and characterized mainly by impaired suppression of the endogenous glucose production.